Preliminary Design of Archimedean Screw Turbine Prototype for Remote Area Power Supply - Fiardi, Erino (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This paper is aimed to design a prototype of screw turbine for power generation. Using principles of velocity vector, the governing equations have been identified for an ideal case of force acting on blade. The paper also describes the conception of a screw turbine rotor for remote area electricity production. The research is done by calculating based on theoretical way and compared with experimental results. Output power can be generated by this small size of turbine is 0.236 watt theoretically and 0.098 watt experimentally. Various losses in the system are discussed, which is also demonstrated that the experimental power outputs and theoretical predictions has a discrepancy. However, it has a great potential to be used for remote area to generated power by using low head water source as this research is developed.